Clinical Characteristics of Patients With HNF1-alpha MODY: A Literature Review and Retrospective Chart Review - Zhao, Qinying; Ding, Li; Yang, Ying; Sun, Jinhong; Wang, Min; Li, Xin; Liu, Ming (Frontiers in Endocrinology, 2022)
Clinical manifestation of hepatocyte nuclear factor-1-alpha (HNF1-alpha) maturity-onset diabetes of the young (MODY) is highly variable. This study aims to investigate the clinical characteristics of patients with HNF1-alpha MODY in general, and by geographical regions (Asian or non-Asian), HNF1-alpha mutations and islet autoantibody status. A literature review and chart review of patients with HNF1-alpha MODY was performed. Means and proportions from studies were pooled using the inverse variance method for pooling, and subgroup analyses were performed. A total of 109 studies involving 1325 patients (41.5% [95% confidence interval [CI] 35.2, 48.1] male) were identified. Mean age of diagnosis was 20.3 years (95% CI 18.3, 22.2), and mean glycated hemoglobin (HbA1c) was 7.3 % (95% CI 7.2, 7.5). In comparison, Asian patients exhibited significantly higher HbA1c (p = 0.007), 2-hour post-load C-peptide levels (p = 0.012), lower levels of triglyceride (TG) (p < 0.001), total cholesterol (TC) (p < 0.001) and high-density lipoprotein cholesterol (HDL-c) (p < 0.001), and less often had macrovascular complications (p = 0.014). Age of diagnosis was oldest in patients with mutations in transactivation domain (p < 0.001). Levels of 2-hour post-load C-peptide (p < 0.001), TG (p = 0.007), TC (p = 0.017) and HDL-c (p = 0.001) were highest, while the prevalence of diabetic neuropathy were lowest (p = 0.024) in patients with DNA-binding domain mutations. Fasting (p = 0.004) and 2-hour post-load glucose (p = 0.003) levels, and the prevalence of diabetic neuropathy (p = 0.010) were higher among patients with positive islet autoantibodies. The study demonstrated that clinical manifestations of HNF1-alpha MODY differed by geographical regions, HNF1-alpha mutations, and islet autoantibody status.